Relationships of emotional regulation difficulties and personality factors with life satisfaction of university students - Castro, Nelson (2021)
Background: The ability to efficiently regulate emotions may be essential for young university students to face the stressful events that occur in their daily life, thus preventing the possibility of suffering anxiety, depression, behavioral problems and poor academic performance. Objectives: The present study aimed to analyze the relationship that difficulties in emotional regulation and personality have with life satisfaction. Method: This correlational and cross-sectional study was conducted with 250 male and female students from a Chilean public university. Results: The results showed that the participants’ life satisfaction is significantly associated with both difficulties in emotional regulation (negatively) and personality dimensions (negatively with neuroticism and positively with the other traits). However, a regression analysis determined that only emotional inattention, responsibility and neuroticism were important predictors of the participants’ life satisfaction. Conclusions: Although all the variables showed a relationship with the students’ life satisfaction, only some of them seemed to predict it. Authorship contribution All authors participated equally and actively in each of the stages of this research; in the design of the study, administration of the techniques, analysis and interpretation of the data, discussion and final revision of the manuscript.